HUBUNGAN POWER OTOT LENGAN DAN BAHU DENGAN KEMAMPUAN LONG SERVICE DALAM PERMAINAN BULUTANGKIS PADA KLUB PB WAHANA SILVA PEKANBARU - Wendy Fauzan; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problems of this researchs based on the preliminary firts observations made in Badminton Club PB Wahana  Silva Pekanbaru there are several obstacles, in particular on the basic techniques of long service is lacking and visible from the swing and accuration shuttlecock on the racket. Results of shuttlecock servicing also often located in the middle area of the field or responsibility and should be far backward the ball right at the back of the field opposite field the line, it is because they lack of the ability explosive power of arms and the shoulders  was owned athletes. The purpose of this research To know Relations Power Arm and Shoulder Muscles using two hand medicine ball test later put Long Service Capabilities in the Game of Badminton in club PB Wahana Silva Pekanbaru using long service tests.The populations in this study are all junior athletes Badminton Club PB Wahana Silva Pekanbaru was totaling 12 peoples. Relative populations is not so great, was according to their ability and time available, the researchers determined the entire population being sampled or the total sampling. Instruments used in this research is to test Two-Hand Medicine Ball-put and test Servis length. Data were analyzed was using product moment correlation Correlation is a statistical tool, to measure the linear relationship between two or more variables. Based on the research that has been described in the previous chapter can be stated the conclusion that there is no significant relationship between the power arms and shoulders (X) with long service (Y) club PB Wahana Silva Pekanbaru, obtainedrcount = 0.374 <rtable = 0.602 , Key Words: Muscle Power Arm And Shoulder, Long Service